Sir Cumference and the dragon of pi : a math adventure - Neuschwander, Cindy; Geehan, Wayne (Watertown, MA : Charlesbridge, 1999)
Radius, son of Sir Cumference, embarks on a quest to find the magic number known as pi in order to restore his father--who has been turned into a dragon--to his original shape.
5.1.
5.1
3-6
Keywords: Circle -- Juvenile literature; Pi -- Juvenile literature; Circle; Pi; Circle; Pi